Bicontinuous phase solid polymer electrolyte and preparation method thereof
By using bicontinuous phase solid polymer electrolyte in the integrated structure and energy storage electrolyte, combining the ratio of lithium salt to ionic liquid and nanofillers, the problems of low mechanical strength and ionic conductivity are solved, and high mechanical strength and high ionicity are achieved The balance of conductivity improves the performance of structural batteries and supercapacitors.
Patent Information
- Application Number
- CN202411783821.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-01-07
AI Technical Summary
The existing structural energy storage integrated electrolyte has poor mechanical strength and low ionic conductivity, making it difficult to achieve a balance between mechanical properties and electrochemical properties.
Bicontinuous phase solid polymer electrolyte is used, consisting of a porous polymer-enhanced matrix and an ion transport phase dispersed therein. The mass ratio of lithium salt to ionic liquid is 1: (3-5.5), and the mass of ionic liquid and thermosetting resin. The ratio is 1: (0.4-2.4), and nanofillers are added in the polymer reinforced matrix to improve mechanical strength and ionic conductivity through the combination of lithium salt and ionic liquid.
The balance between high mechanical strength and high ionic conductivity is achieved, the loss of ionic liquid is avoided, and the high ionic conductivity is maintained for a long time is significantly improved, which is the electrochemical and mechanical properties of structural batteries and supercapacitors.
Smart Images

Figure CN119275341A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of secondary batteries, and in particular relates to a dual-continuous phase solid polymer electrolyte and a preparation method thereof. Background Art
[0002] New energy vehicles, electric vehicles and portable mobile devices have entered a rapid development stage. They need to have sufficient energy storage performance, structural bearing capacity, lightweight design, high safety standards and eco-friendliness. Current energy storage devices cannot meet these design requirements at the same time. Structural-energy storage integrated composite materials are a reasonable solution. Structural-energy storage integrated composite materials have both load-bearing and energy storage functions. They can replace some traditional load-bearing components and have sufficient energy storage capacity while achieving lightweight body. At present, most structural energy storage integrated devices use carbon fiber as reinforcement and electrode, which has the advantages of large theoretical energy storage capacity and fast charging and discharging. Another key technology for structural energy storage integration is the construction of structural electrolytes. Ideal electrolytes have both high ionic conductivity and mechanical strength.
[0003] The electrolytes suitable for structural energy storage integration mainly include solid electrolytes and gel electrolytes. Inorganic electrolytes have the disadvantages of poor mechanical properties and high costs in some cases, polymer electrolytes have low ion conductivity, and gel electrolytes have the disadvantage of low mechanical strength. It is difficult to achieve a balance between mechanical properties and electrochemical properties.
[0004] For example, patent application CN118538989A discloses a method for preparing a composite solid electrolyte membrane and its application, including a co-solvent-modified sulfide electrolyte, a composite polymer electrolyte and an inorganic additive, which are prepared into an all-solid-state soft-pack battery to improve the cycle life and capacity retention rate of the battery. However, the high cost of sulfide electrolytes limits the development of marketization.
[0005] Patent application CN107275119A designs a polyethylene oxide-bisphenol A epoxy resin-ionic liquid all-solid polymer electrolyte used in supercapacitors, patent application CN118398885A discloses a solid-liquid dual-phase structure electrolyte and applies it to lithium batteries, and patent application CN118645702A involves a method for preparing a high-mechanical porous structure electrolyte. The solid electrolytes disclosed in these three patent applications all involve the use of chemical substances with amino groups and epoxy resins to cross-link and solidify the support structure of the electrolyte, and the problem of low ionic conductivity has not been effectively solved. Summary of the invention
[0006] In order to solve the problems of poor mechanical strength and low ionic conductivity of electrolytes used for structural energy storage integration, the present invention provides a dual-continuous phase solid polymer electrolyte and a preparation method thereof. The technical solution adopted by the present invention is as follows: A dual-continuous phase solid polymer electrolyte, the solid polymer electrolyte consists of a porous polymer reinforced matrix and an ion transport phase dispersed in the polymer reinforced matrix; the polymer reinforced matrix is made of a thermosetting resin; the ion transport phase consists of an ionic liquid and a lithium salt, the mass ratio of the lithium salt to the ionic liquid is 1:(3-5.5), and the mass ratio of the ionic liquid to the thermosetting resin is 1:(0.4-2.4); the ionic liquid is a combination of one or more of an imidazole ionic liquid, a quaternary ammonium salt ionic liquid or a pyrrole ionic liquid; the lithium salt is an imine lithium salt.
[0007] Preferably, the lithium salt is lithium bis(difluorosulfonyl)imide or lithium bis(trifluoromethylsulfonyl)imide.
[0008] Preferably, the thermosetting resin is a combination of one or more of bisphenol A diglycidyl ether, bisphenol F type epoxy resin, E type epoxy resin, tetraglycidylamine type epoxy resin, and bisphenol S type epoxy resin.
[0009] Preferably, the dual-continuous phase solid polymer electrolyte also contains nanofillers accounting for 1 to 5 wt% of the total mass of the polymer reinforced matrix and the ion transport phase. The nanofillers are dispersed in the polymer reinforced matrix and the ion transport phase and are selected from one or more of nano titanium oxide, aluminum oxide, MOF metal organic framework, and COF covalent organic framework.
[0010] The preparation method of the dual-continuous phase solid polymer electrolyte of the present invention comprises the following steps: 1) Weigh the lithium salt and the ionic liquid in a mass ratio of 1:(3-5.5) and mix them evenly; 2) adding thermosetting resin in a mass ratio of ionic liquid to thermosetting resin of 1:(0.4-2.4), mixing and stirring, and removing bubbles to obtain a liquid dual-continuous phase solid polymer electrolyte precursor; 3) solidifying the liquid dual-phase solid polymer electrolyte precursor to obtain the dual-phase solid polymer electrolyte.
[0011] Preferably, in step 3), the liquid dual-continuous phase solid polymer electrolyte precursor is cast into a polytetrafluoroethylene mold that has been uniformly preheated to 110-140°C, heated at 100-120°C for 2-3 hours, and then cured at 50-70°C for 6-12 hours to obtain the dual-continuous phase solid polymer electrolyte.
[0012] Preferably, in step 2), before adding the thermosetting resin, 1 to 5 wt% of the total mass of the polymer reinforcement matrix and the ion transport phase is weighed and added.
[0013] Preferably, a cross-linking agent is also added when adding the thermosetting resin in step 2), and the cross-linking agent is one or more of polyethylene glycol, propylene glycol triglycidyl ether, pentaerythritol glycidyl ether, and tetraglycidylamine type epoxy resin, and the mass ratio of the thermosetting resin to the cross-linking agent is (5-10):1.
[0014] Preferably, the method for removing bubbles in step 2) is by vacuuming, standing or adding a defoaming agent.
[0015] The dual-continuous phase solid polymer electrolyte of the present invention is used to form a supercapacitor together with a positive electrode sheet, a separator and a negative electrode sheet.
[0016] Beneficial effects of the present invention: The dual-continuous phase solid polymer electrolyte of the present invention has both a polymer matrix and an ion transport phase, and has high mechanical strength and high ion conductivity. At the same time, the ion transport phase is dispersed in the polymer matrix to avoid the loss of ionic liquid in the ion transport phase, so that the dual-phase structural electrolyte can maintain high ion conductivity for a long time and has long-term stability. The dual-continuous phase solid polymer electrolyte is used in structural batteries or supercapacitors, which can make the structural batteries have excellent electrochemical and mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 Schematic diagram of the structure of a dual-continuous phase solid polymer electrolyte.
[0018] Figure 2 Structural diagram of a supercapacitor composed of a dual-phase solid polymer electrolyte.
[0019] Figure 3 Comparative Examples 1, 2, and 3 are shown in the cured state.
[0020] Figure 4 Scanning electron microscope image of the dual-continuous phase solid polymer electrolyte obtained in Example 1-1.
[0021] Figure 5 Scanning electron microscope image of the dual-continuous phase solid polymer electrolyte obtained in Example 1-2. DETAILED DESCRIPTION
[0022] In order to make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0023] Unless otherwise defined, all technical terms and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0024] The present invention will be further described below by means of specific examples.
[0025] Example 1
[0026] 1) Lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) and 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide (EMIMTFSI) were fully mixed and stirred at a mass ratio of 1:4 to obtain a mixed ionic liquid.
[0027] 2) adding epoxy resin monomer according to the mass ratio of epoxy resin TJ-2000 and EMIMTFSI of 1:1 and mixing and stirring for 20 minutes, and vacuuming to remove bubbles to obtain a dual-continuous phase solid polymer electrolyte precursor; 3) Casting the dual-continuous phase solid polymer electrolyte precursor in a polytetrafluoroethylene mold preheated at 120° C., curing at 120° C. for 2 hours, and further curing at 60° C. for 12 hours to obtain a dual-continuous phase solid polymer electrolyte.
[0028] Example 2
[0029] The difference between this embodiment and embodiment 1 is that in step 1), the mass ratio of LiTFSI:EMIMTFSI is 1:5.5.
[0030] Example 3
[0031] 1) Weigh the above raw materials according to the mass ratio of LiTFSI: EMIMTFSI: nano-titanium oxide of 1:4:0.2, mix the above raw materials thoroughly, and then ultrasonically disperse them for 4 hours to obtain a mixed ionic liquid; 2) adding epoxy resin monomer according to the mass ratio of epoxy resin TJ-2000 and EMIMTFSI of 1:1 and mixing and stirring for 20 minutes, and vacuuming to remove bubbles to obtain a dual-continuous phase solid polymer electrolyte precursor; 3) Casting the dual-continuous phase solid polymer electrolyte precursor into a polytetrafluoroethylene mold preheated at 120°C, curing at 120°C for 2 hours, and further curing at 60°C for 12 hours to obtain a dual-continuous phase solid polymer electrolyte.
[0032] Example 4
[0033] 1) LiTFSI:EMIMTFSI were fully mixed and stirred at a mass ratio of 1:4 to obtain a mixed ionic liquid; 2) The mixed ionic liquid, epoxy resin TJ-2000, and propylene glycol triglycidyl ether were mixed in a mass ratio of 8:8:1 and stirred for 20 minutes, and the bubbles were removed by vacuum to obtain a dual-continuous phase solid polymer electrolyte precursor.
[0034] 3) Casting the dual-continuous phase solid polymer electrolyte precursor into a polytetrafluoroethylene mold preheated at 120°C, curing at 120°C for 2 hours, and further curing at 60°C for 12 hours to obtain a dual-continuous phase solid polymer electrolyte.
[0035] Example 5
[0036] The difference between this embodiment and embodiment 4 is that in step 2), propylene glycol triglycidyl ether is replaced by pentaerythritol glycidyl ether.
[0037] Example 6
[0038] The difference between this embodiment and embodiments 4 and 5 is that in step 2), AG-80 (tetraglycidylamine type epoxy resin) is used to replace glycerol triglycidyl ether or pentaerythritol glycidyl ether.
[0039] Example 7
[0040] 1) LiTFSI: EMIMTFSI: nano-titanium oxide were fully mixed and stirred at a mass ratio of 1:4:0.2, and ultrasonically dispersed for 4 hours to obtain a mixed ionic liquid; 2) The mixed ionic liquid, epoxy resin TJ-2000 and AG-80 were mixed in a mass ratio of 8:8:1 and stirred for 20 minutes, and the bubbles were removed by vacuum to obtain a dual-continuous phase solid polymer electrolyte precursor.
[0041] The liquid electrolyte precursor was cast into a polytetrafluoroethylene mold preheated at 120°C, cured at 120°C for 2 hours, and further cured at 60°C for 12 hours to obtain a dual-continuous phase solid polymer electrolyte.
[0042] Comparative Example 1
[0043] The epoxy resin TJ-2000 monomer was cast into a mold preheated at 120 degrees Celsius and cured at 120 degrees Celsius for 12 hours.
[0044] Comparative Example 2
[0045] The epoxy resin TJ-2000 monomer and 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt (EMIMTFSI) were mixed and stirred at a mass ratio of 1:1 for half an hour, cast in a mold preheated at 120 degrees Celsius, and cured at 120 degrees Celsius for 12 hours.
[0046] Comparative Example 3
[0047] LiTFSI was dissolved in acetone (acetone was used as a solvent and did not react directly with the epoxy ring), epoxy resin TJ-2000 monomer and LiTFSI were mixed and stirred at a mass ratio of 4:1 for half an hour, cast in a mold preheated at 120 degrees Celsius, and cured at 120 degrees Celsius for 12 hours.
[0048] Table 1 Tensile modulus and ionic conductivity of dual-phase solid polymer electrolytes Lithium salts: ionic liquids Ionic liquid content additive Curing temperature Tensile modulus (MPa) Ionic conductivity (S / cm) Example 1 1:4 50% none 120 573 0.00076 Example 2 1:5.5 50% none 120 333 0.0005 Example 3 1:4 50% <![CDATA[TiO2]]> 120 646 0.0011 Example 4 1:4 50% 3 functional group PEG 120 440 0.001 Example 5 1:4 50% 4-functional PEG 140 0.00083 Example 6 1:4 50% AG80 120 496 0.000047 Example 7 1:4 50% <![CDATA[AG80+TiO2]]> 120 556 0.0005 Through the above examples, it was found that the epoxy resin still solidified without adding a curing agent. Therefore, it can be inferred that the components in the mixed ionic liquid can catalyze the ring opening of the epoxy group (COC) to cause the epoxy resin to undergo addition polymerization. In previous reports, some ionic liquids can be used as curing agents for epoxy resins. In Comparative Example 1, the epoxy resin monomer still maintained a viscous and transparent state at the curing temperature, and no polymerization occurred. In Comparative Example 2, due to the addition of ionic liquids, the epoxy resin monomer solidified, but the curing process was slow, and it was completely cured after 12 hours. The surface of the cured epoxy resin turned yellow, and the bottom was white, showing aging. Comparative Example 3 also solidified, and the cured epoxy resin was nearly transparent. Due to the dissolution and volatilization of acetone, there were obvious holes and a hard texture. It can be inferred that the added lithium salt can cure the epoxy resin. The main reason is that the imine groups in these lithium salts can undergo a ring-opening addition reaction with the epoxy group (COC) in the epoxy resin to form a three-dimensional cross-linked network, and the activity of lithium sulfonyl imide is relatively large, which can reduce the cross-linking curing temperature. Lithium ions in lithium imide (Li + ) and iminium anions (such as TFSI - ) can interact with epoxy resin molecules. These ionic interactions can promote the arrangement and cross-linking between epoxy resin molecules and enhance the electrochemical properties of the cured material.
[0049] Further comparison of the tensile modulus and ionic conductivity of the dual-continuous phase solid polymer electrolyte in Table 1 shows that lithium salt can cure epoxy resin and achieve good mechanical and electrochemical properties. And to a certain extent, increasing the ratio of lithium salt to ionic liquid can improve the tensile modulus and ionic conductivity. Figure 5 The electron microscope image is when the mass ratio of lithium salt to ionic liquid is 1:5.5. When the ratio is 1:4, the tensile modulus of the prepared electrolyte is 573MPa and the ionic conductivity is 0.00076 S / cm. Figure 4 This is a scanning electron microscope image of an electrolyte with a lithium salt to ionic liquid content ratio of 1:4, which has a relatively uniform three-dimensional network that can achieve mechanical support and ion conduction.
[0050] As shown in Table 1, Example 3, after adding 2% nano titanium oxide, the electromechanical properties of the electrolyte are significantly improved, the tensile modulus reaches 646MPa, and the ionic conductivity rises to 0.0011 S / cm. Comparison of Examples 4 to 6 shows that the tensile modulus and ionic conductivity fluctuate after adding different chemical additives, and the ionic conductivity increases to 0.001 S / cm after adding trifunctional PEG. It can have both high mechanical strength and high ionic conductivity, and can be used in supercapacitors (structural batteries).
[0051] The dual-phase structure electrolytes prepared in Examples 1 to 7 were assembled into a pair of supercapacitors, and the electrodes on both sides of the dual-continuous phase solid polymer electrolyte in the supercapacitors were both carbon fiber cloths.
[0052] In the present invention, the dual-continuous phase solid polymer electrolyte may be in the form of a film, a block, etc., and is selected and configured specifically according to the needs of the actual energy storage device.
[0053] The thermosetting resin includes at least one of bisphenol A diglycidyl ether, bisphenol F type epoxy resin, E type epoxy resin (such as epoxy resin E51), tetraglycidylamine type epoxy resin (such as epoxy resin AG-80), and bisphenol S type epoxy resin, but is not limited thereto.
[0054] In other embodiments, the ionic liquid may be an imidazole ionic liquid, a quaternary ammonium salt ionic liquid, and a pyrrole ionic liquid. The imidazole ionic liquid includes at least one of 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide (EMIMTFSI), 1-ethyl-3-methylimidazolium tetrafluoroborate (EMIMBF4), N-methyl-N-methoxyethylpyrrolidine bis(trifluoromethanesulfonyl)imide ([MEMP][TFSI]), 1-methyl-1-propylpiperidinium bis(trifluoromethanesulfonyl)imide (PP13FSI), 1-butyl-1-methylpyrrolidine bis(trifluoromethanesulfonyl)imide (BMPTFSI), and 1-ethyl-3-methylimidazolium chloride ([EMIm]Cl), but is not limited thereto.
[0055] In other embodiments, the mass ratio of the ionic liquid to the polymer matrix is 1:(0.4-2.4), for example, it can be 70:30, 60:40, 55:45, 50:50, 55:45, 40:60, 30:70, etc.
[0056] In other embodiments, the mass ratio of the lithium salt to the ionic liquid is 1:(3-5.5), for example, 1:3, 1:4, 1:5 or 1:5.5.
[0057] In other embodiments, fillers accounting for 1% to 5%, such as 1%, 2%, 3%, 4%, 5%, etc., are added to the dual-continuous phase solid polymer electrolyte.
[0058] Nanofillers, nanofillers are dispersed in the polymer matrix and the ion transport phase; including nano oxides such as nano titanium oxide and aluminum oxide, and nanofillers can reduce the crystallinity of the polymer and increase the amorphous phase area, thereby facilitating the migration of lithium ions. In addition, fast lithium ion channels can be formed near the filler particles, increasing the mechanical properties of the polymer matrix and making it easy to form a film. Nanofillers can produce uniform lithium flux by regulating the ion transport behavior in the electrolyte bulk phase, thereby inhibiting the generation of lithium dendrites from the root. At the same time, nanofillers can significantly enhance the mechanical strength of the electrolyte and inhibit the growth of lithium dendrites. Nanofillers can improve the interface compatibility between the electrolyte and the electrode. Due to the special structure of nanofillers, such as nanowires, three-dimensional network structures and vertically arranged structures, the ion migration rate can be increased, thereby improving the interface stability. The surface polymers of nanofillers have abundant polar groups, which can promote the dissociation of lithium salts and enhance the ion transport capacity through Lewis acid-base interactions.
[0059] In other embodiments, the nanofiller can also be a metal organic framework (MOF), which has a regular pore size and a large specific surface area, providing a fast channel and a large number of reaction sites for ion transport. The open metal sites of MOF can promote the dissociation of lithium salts and fix anions through Lewis acid-base interactions, thereby obtaining good lithium ion mobility and a high migration number. The one-dimensional pores of the MOF material can be used as a diffusion channel for Li+, thereby effectively homogenizing the deposition of Li+.
[0060] In other embodiments, a crosslinking agent is added in the step of preparing a dual-continuous phase solid polymer electrolyte precursor, and the crosslinking agent is selected from one or more of polyethylene glycol, propylene glycol triglycidyl ether, pentaerythritol glycidyl ether, and tetraglycidylamine epoxy resin. The introduction of ether bonds can effectively dissociate lithium salts and increase the number of free ions, thereby improving the ionic conductivity of the electrolyte. The introduction of ether bonds can form fast ion conduction channels, thereby effectively homogenizing Li + The deposition of MgO can also improve the electrochemical stability and electrode-electrolyte interface compatibility.
[0061] The structure of the supercapacitor in the prior art includes a positive electrode 1, a separator, a negative electrode 3, and an electrolyte 4 stacked in order from top to bottom. In the above-mentioned supercapacitor (structural battery), the electrolyte preparation method is to first prepare a resin skeleton and then soak it in an ionic liquid, and the impedance is relatively large. Based on this, an embodiment of the present invention also provides a structural battery, wherein, as Figure 2As shown, the supercapacitor includes an electrolyte 4, and a positive electrode sheet 1, a separator 2, and a negative electrode sheet 3 stacked in sequence in the electrolyte 4. Specifically, the positive electrode sheet 1 includes a positive electrode current collector and a dressing layer located on the surface of the positive electrode current collector, and the negative electrode sheet 3 includes a negative electrode current collector and a dressing layer located on the surface of the negative electrode current collector. The difference is that the electrolyte of the present invention simplifies the preparation steps through an integrated molding method, reduces the waste of ionic liquid, and makes the solid and liquid phases more coherent.
[0062] In other embodiments, both the positive electrode current collector and the negative electrode current collector are carbon fiber current collectors. In this case, the structural battery (supercapacitor) can be used in new energy vehicles, drones, aerospace, flying cars and other fields.
[0063] The present invention also provides a method for preparing a structural energy storage integrated structure battery, wherein: Figure 2 As shown, the following steps are included: 1) coating the positive electrode slurry (cobalt oxide, nickel manganese cobalt oxide, LiFePO4 and lithium manganate) on the carbon fiber current collector and drying it to obtain a positive electrode sheet 1; 2) coating the negative electrode slurry (graphite) on the carbon fiber current collector and drying it to obtain the negative electrode sheet 3; 3) The positive electrode sheet 1, the diaphragm 2 (glass fiber cloth or foam diaphragm) and the negative electrode sheet 3 are stacked and placed in a mold, and the dual-continuous phase solid polymer electrolyte precursor 4 is poured therein, heated at a temperature of 100-140°C for 2-3h, and integrally cured and formed, and then cured at 50-70°C to obtain the integrated structure supercapacitor, which includes a supercapacitor electrolyte layer 4 (specifically a dual-phase structure electrolyte), and the positive electrode sheet 1, the diaphragm 2 and the negative electrode sheet 3 stacked in sequence and located in the electrolyte layer 3.
[0064] The positive electrode slurry includes a positive electrode active material, a conductive agent, a binder and a solvent, and the negative electrode slurry includes a negative electrode active material, a conductive agent, a binder and a solvent.
[0065] The conductive agent, adhesive and solvent are prior art and will not be described in detail here.
[0066] In summary, the embodiment of the present invention provides a dual-continuous phase solid polymer electrolyte and a preparation method thereof. The present invention uses lithium imide to cure epoxy resin. The polymer reinforcement phase matrix in the dual-continuous phase solid polymer electrolyte provided can ensure that the dual-phase structure electrolyte has a sufficiently high mechanical strength, and the ion transport phase in the dual-phase structure electrolyte can ensure that the dual-phase structure electrolyte has a sufficiently high ion conductivity. At the same time, the ion transport phase is dispersed in the polymer reinforcement phase matrix to avoid the loss of ionic liquid in the ion transport phase, so that the dual-continuous phase solid polymer electrolyte can maintain high ion conductivity for a long time. Therefore, the dual-continuous phase solid polymer electrolyte has long-term stability.
[0067] The dual-continuous phase solid polymer electrolyte is used in a supercapacitor (or a structural battery), so that the supercapacitor has excellent electrochemical and mechanical properties.
[0068] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.
Claims
1. A dual-continuous phase solid polymer electrolyte, characterized in that: The solid polymer electrolyte is composed of a porous polymer reinforced matrix and an ion transport phase dispersed in the polymer reinforced matrix; the polymer reinforced matrix is made of a thermosetting resin; the ion transport phase is composed of an ionic liquid and a lithium salt, the mass ratio of the lithium salt to the ionic liquid is 1:(3-5.5), and the mass ratio of the ionic liquid to the thermosetting resin is 1:(0.4-2.4); the ionic liquid is a combination of one or more of an imidazole ionic liquid, a quaternary ammonium salt ionic liquid or a pyrrole ionic liquid; and the lithium salt is an imide lithium salt.
2. The dual-continuous phase solid polymer electrolyte according to claim 1, characterized in that: The lithium salt is lithium bis(difluorosulfonyl)imide or lithium bis(trifluoromethylsulfonyl)imide.
3. The dual-continuous phase solid polymer electrolyte according to claim 1, characterized in that: The thermosetting resin is a combination of one or more of bisphenol A diglycidyl ether, bisphenol F type epoxy resin, E type epoxy resin, tetraglycidylamine type epoxy resin, and bisphenol S type epoxy resin.
4. The dual-continuous phase solid polymer electrolyte according to claim 1, characterized in that: The dual-continuous phase solid polymer electrolyte also contains nanofillers accounting for 1 to 5 wt% of the total mass of the polymer reinforced matrix and the ion transport phase. The nanofillers are dispersed in the polymer reinforced matrix and the ion transport phase and are selected from one or more of nano titanium oxide, aluminum oxide, MOF metal organic framework, and COF covalent organic framework.
5. The method for preparing a dual-continuous phase solid polymer electrolyte according to claim 1, characterized in that: The steps of this method are as follows: 1) Weigh the lithium salt and the ionic liquid in a mass ratio of 1:(3-5.5) and mix them evenly; 2) adding thermosetting resin in a mass ratio of ionic liquid to thermosetting resin of 1:(0.4-2.4), mixing and stirring, and removing bubbles to obtain a liquid dual-continuous phase solid polymer electrolyte precursor; 3) solidifying the liquid dual-phase solid polymer electrolyte precursor to obtain the dual-phase solid polymer electrolyte.
6. The method for preparing a dual-continuous phase solid polymer electrolyte according to claim 5, characterized in that: In step 3), the liquid dual-continuous phase solid polymer electrolyte precursor is cast into a polytetrafluoroethylene mold that has been uniformly preheated to 110-140° C., heated at 100-120° C. for 2-3 hours, and then cured at 50-70° C. for 6-12 hours to obtain the dual-continuous phase solid polymer electrolyte.
7. The method for preparing a dual-continuous phase solid polymer electrolyte according to claim 5, characterized in that: In step 2), before adding the thermosetting resin, weigh 1 to 5 wt% of the total mass of the polymer reinforcement matrix and the ion transport phase, and add the nanofiller.
8. The method for preparing a dual-continuous phase solid polymer electrolyte according to claim 5, characterized in that: When adding the thermosetting resin in step 2), a crosslinking agent is also added. The crosslinking agent is one or more of polyethylene glycol, propylene glycol triglycidyl ether, pentaerythritol glycidyl ether, and tetraglycidylamine type epoxy resin. The mass ratio of the thermosetting resin to the crosslinking agent is (5-10):
1.
9. The method for preparing a dual-continuous phase solid polymer electrolyte according to claim 5, characterized in that: In step 2), the method for removing bubbles is to use vacuuming, standing or adding a defoaming agent.
10. Use of the dual-continuous phase solid polymer electrolyte according to claim 1 in forming a supercapacitor together with a positive electrode sheet, a separator and a negative electrode sheet.
Citation Information
Patent Citations
Polyethylene oxide-bisphenol A epoxy resin-ionic liquid all-solid polymer electrolyte and application thereof
CN107275119A
Preparation method and application of composite solid electrolyte membrane
CN118538989A
High-mechanical porous structure electrolyte as well as preparation method and application thereof
CN118645702A
Fiber-like-structured lithium ion battery and preparation method
CN107591559A
Bicontinuous phase gel polymer electrolyte as well as preparation method and application thereof
CN116505064A
Cited By
Resin-based electrolyte, preparation method thereof and application of resin-based electrolyte in structural energy storage composite material
CN119965338A